Strategi Peningkatan Pertumbuhan dan Hasil Tanaman Kedelai yang Terpapar Sinar UV-B - Suyadi, Aman (UM Purwokerto Press, 2024)
Strategi Peningkatan Pertumbuhan dan Hasil Tanaman Kedelai yang Terpapar Sinar UV-B